Medication Adherence Mediates the Association between Type D Personality and High HbA1c Level in Chinese Patients with Type 2 Diabetes Mellitus: A Six-Month Follow-Up Study - Xuemei Li; Min Gao; Shengfa Zhang; Huiwen Xu; Huixuan Zhou; Xiaohua Wang; Zhiyong Qu; Jing Guo; Weijun Zhang; Donghua Tian (Journal of Diabetes Research)
Aims. To examine the association between Type D personality and HbA1c level and to explore the mediating role of medication adherence between them in patients with type 2 diabetes mellitus (T2DM). Methods. 330 patients went on to complete a self-report measure of medication adherence and the HbA1c tests. Chi-square test, T test, Ordinary Least Square Regression (OLS), and Recentered Influence Function Regression (RIF) were employed. Results. Patients with Type D personality had significantly higher HbA1c value (P<0.01). When Type D personality was operationalized as a categorical variable, SI was associated with HbA1c (P<0.01). When NA, SI, and their interaction term were entered into regression, all of them were no longer associated with HbA1c level (P>0.1). On the other hand, when Type D personality was operationalized as a continuous variable, only SI trait was associated with HbA1c level (P<0.01). When NA, SI, and NA×SI term together were entered into regression, only SI was not related to HbA1c level. Furthermore, medication adherence had a significant mediation effect between Type D personality and HbA1c, accounting for 54.43% of the total effect. Conclusion. Type D personality was associated with HbA1c in direct and indirect ways, and medication adherence acted as a mediator role.